The Al Khudairah Necropolis (Sharjah, UAE): Reflections from the 2023 Field Season - del Cerro Linares, Carmen; Fernández Rodríguez, Carlos; Gómez Sanz, Paula; Alonso García, Alicia; González Martín, Armando (Études et Travaux, 2024)
The necropolis from Jebel al Khudairah, located in the Central Region of the Emirate of Sharjah (United Arab Emirates) witnessed excavations in 2020 and 2023 from members of the Spanish Archaeological and Archaeobiological Mission at Sharjah, drawn from Universidad Autónoma de Madrid. In this paper we present a preliminary overview of the results from these two field seasons after completing excavations of five tombs of very diverse types, located in several sectors of the jebel. Only one of them provided remains of burials of at least two individuals accompanied by a metal arrowhead. Nevertheless, the preliminary comparative analysis of the architecture of the structures as well as of the only datable find, allows one to make some suggestions concerning the chronological span of the necropolis.